2014
DOI: 10.4049/jimmunol.1302061
|View full text |Cite
|
Sign up to set email alerts
|

Infection-Induced Changes in Hematopoiesis

Abstract: The bone marrow is an important site for the interrelated processes of hematopoiesis, granulopoiesis, erythropoiesis and lymphopoiesis. A wide variety of microbial challenges are associated with profound changes in this compartment that impact on hematopoietic differentiation and mobilization of a variety of cell types. This article reviews some of the key pathways that control BM homeostasis, the infectious and inflammatory processes that affect the BM, and how addressing the knowledge gaps in this area has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 107 publications
2
74
0
Order By: Relevance
“…Rather, emergency hematopoiesis has been described in a number of infectious events and in response to other TLR agonists. [37][38][39][40][41] One important difference between flagellin and such agonists is that flagellin does not induce large amounts of master proinflammatory cytokines such as tumor necrosis factor a and IL-12 p70, enabling it to be administered repeatedly at doses similar to those used here without significant clinical-type adverse events. Another difference is that some TLR agonists are reported to directly act upon LSK cells, which was not the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, emergency hematopoiesis has been described in a number of infectious events and in response to other TLR agonists. [37][38][39][40][41] One important difference between flagellin and such agonists is that flagellin does not induce large amounts of master proinflammatory cytokines such as tumor necrosis factor a and IL-12 p70, enabling it to be administered repeatedly at doses similar to those used here without significant clinical-type adverse events. Another difference is that some TLR agonists are reported to directly act upon LSK cells, which was not the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Under conditions of stress, such as injury or infection, hematopoiesis can increase in capacity, to provide the blood cells necessary to promote inflammation, wound healing, and/or the elimination of pathogens. [3][4][5][6][7] Although coordinated alterations in hematopoiesis can be beneficial, dysregulated responses can result in the development of unchecked inflammation and thus contribute to various disease states, including colitis, asthma, and allergies. 6,[8][9][10] Moreover, recent studies have demonstrated that the contributions of hematopoiesis to the development of inflammation are not limited to events occurring in the bone marrow, and that hematopoietic progenitor cells can enter the periphery and traffic directly to sites of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…When vertebrates are infected by pathogens such as bacteria, the immune cells, particularly mononuclear (monocytes/macrophages) and polymorphonuclear (granulocytes) myeloid phagocytes, respond immediately1. A slight infection such as a localised bacterial challenge induces the recruitment of myeloid phagocytes, particularly granulocytes, from the bloodstream, but exerts a limited influence on their exhaustion and expansion23.…”
mentioning
confidence: 99%
“…Although these physiologically dormant HSCs quickly enter the cell cycle upon challenge456789, how they react to pathogens remains unclear, primarily because of the difficulty in isolating pure HSCs34. However, the response of HSPCs and their subsequent developmental potential under demand-derived emergency conditions, such as when encountering pathogens or when stimulated by cytokines, has been the focus of research recently146. Different pathogens induce different HSPC reactions6.…”
mentioning
confidence: 99%
See 1 more Smart Citation